IMPLEMENTASI PENDIDIKAN INKLUSI TERHADAP ANAK BERKEBUTUHAN KHUSUS DI SMP NEGERI 37 KOTA SEMARANG - Alif Fahmi, Mohamad; Suprapti, Suprapti (Journal of Physical Activity and Sports (JPAS), 2025)
Mohamad Alif Fahmi. "Implementation of inclusive education for children with special needs at the inclusive school of SMP Negeri 37 Semarang ". Postgraduate, Universitas PGRI Semarang, 2024. The study was based on students with special needs, especially subjects related to physical education to be lacking in knowledge material and appear more prominent in skills or practical activities. Its implementation at SMP Negeri 37 Semarang was only in 2024, but it is still not in accordance with existing provisions. The objectives of this study are: 1.) To know the process of occurrence or the existence of children with special needs. 2.) To know inclusive education is obtained by children with special needs in PJOK learning in the psychomotor aspect. 3.) To know the treatment received by students with special needs from PJOK teachers and regular students both from learning, assessment and activities at school. The results of this study prove that the implementation of inclusive education for children with special needs at SMP Negeri 37 Semarang is already in the good category. Evidence from the results of this study can be seen from the good running of aspects such as planning, implementation and evaluation in the inclusive education program.